A chromosomal-level genome assembly for the insect vector for Chagas disease, Triatoma rubrofasciata. Issue 8 (19th August 2019) - Liu, Qin; Guo, Yunhai; Zhang, Yi; Hu, Wei; Li, Yuanyuan; Zhu, Dan; Zhou, Zhengbin; Wu, Jiatong; Chen, Nansheng; Zhou, Xiao-Nong
Abstract: Background: Triatoma rubrofasciata is a widespread pathogen vector for Chagas disease, an illness that affects approximately 7 million people worldwide. Despite its importance to human health, its evolutionary origin has not been conclusively determined. A reference genome for T. rubrofasciata is not yet available. Finding: We have sequenced the genome of a female individual with T. rubrofasciata using a single molecular DNA sequencing technology (i.e., PacBio Sequel platform) and have successfully reconstructed a whole-genome (680-Mb) assembly that covers 90% of the nuclear genome (757 Mb). Through Hi-C analysis, we have reconstructed full-length chromosomes of this female individual that has 13 unique chromosomes (2n = 24 = 22 + X1 + X2) with a contig N50 of 2.72 Mb and a scaffold N50 of 50.7 Mb. This genome has achieved a high base-level accuracy of 99.99%. This platinum-grade genome assembly has 12, 691 annotated protein-coding genes. More than 95.1% of BUSCO genes were single-copy completed, indicating a high level of completeness of the genome. Conclusion: The platinum-grade genome assembly and its annotation provide valuable information for future in-depth comparative genomics studies, including sexual determination analysis in T. rubrofasciata and the pathogenesis of Chagas disease.